MISCONCEPTIONS IN LEARNING GROUP THEORY : CASE STUDY PRE-SERVICE MATHEMATIC TEACHERS - Subroto, Toto; Suryadi, Didi; Rosjanuardi, Rizky (Journal of Authentic Research on Mathematics Education (JARME), 2023)
This study aims to explore the misconceptions that occur in group theory learning conducted by pre-service mathematic teachers.  This research is part of a long research from abstraction in learning group theory: study of hermeneutic phenomenology on pre-service mathematics teachers.  This research method uses case study in qualitative research.  Data obtained in the form of Focus Group Discussion (FGD) videos and pdf files of partisipan diaries.  The findings of this study indicate a misconception on group as set and subset as subgroup and on the inverse element as only one over in multiplication.  These two misconceptions show from misunderstanding and misperseption.